2019
DOI: 10.1097/md.0000000000016934
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of IgG4-related kidney disease without extrarenal organ involvement

Abstract: Rationale: IgG4-related disease (IgG4-RD) is a systemic chronic inflammatory disorder that can affect almost every organ. IgG4-RD includes IgG4-related kidney disease (IgG4-RKD), but lesions affecting the kidney alone or first are very rare, and a complete understanding is lacking. Computed tomography (CT) and magnetic resonance imaging (MRI) findings can show the typical characteristics of IgG4-RKD and provide information for accurate and rapid diagnosis. Patient concerns: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Among the cases of IgG4-RD affecting the renal pelvis or perirenal fat reported in the literature, 53.8% (7/13) underwent nephrectomy or nephroureterectomy, and the pathological diagnosis was IgG4-RKD[ 13 - 17 ]. From our literature review, we found that the misdiagnosis rate of IgG4-RD involving the renal pelvis was very high, suggesting that currently, urologists generally lack understanding of this disease[ 18 , 19 ]. This causes a certain delay in the diagnosis and treatment stages.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cases of IgG4-RD affecting the renal pelvis or perirenal fat reported in the literature, 53.8% (7/13) underwent nephrectomy or nephroureterectomy, and the pathological diagnosis was IgG4-RKD[ 13 - 17 ]. From our literature review, we found that the misdiagnosis rate of IgG4-RD involving the renal pelvis was very high, suggesting that currently, urologists generally lack understanding of this disease[ 18 , 19 ]. This causes a certain delay in the diagnosis and treatment stages.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Contrastenhanced CT is an important tool to evaluate the lesions, which exhibit a variety of imaging features of the bilateral kidneys, such as diffuse patchy involvement, multiple lowdensity lesions, extrarenal lesions located on the renal capsule (so-called rim-like lesion), or renal pelvis thickening with smooth intraluminal surface. [42,43] A solitary mass lesion is rare and very difficult to be distinguished from a malignant tumor. [43] The histopathology of IgG4-TIN presents clearly demarcated margins between affected and unaffected areas, which corresponded to the imaging characteristics of multiple low-density lesions, and lymphoplasmacytic cells infiltrate into and beyond the renal capsule, which is a specific distribution of renal parenchymal lesions, and lesions located outside the renal capsule was thought to correspond to the rim-like lesion in imagings.…”
Section: Igg4-related Ophthalmic Disease (Igg4-rod)mentioning
confidence: 99%
“…In addition, elevated serum IgG4 levels are commonly observed in IgG4-TIN, and >50% of patients with active disease present with hypocomplementemia [42] . Contrast-enhanced CT is an important tool to evaluate the lesions, which exhibit a variety of imaging features of the bilateral kidneys, such as diffuse patchy involvement, multiple low-density lesions, extrarenal lesions located on the renal capsule (so-called rim-like lesion), or renal pelvis thickening with smooth intraluminal surface [42,43] . A solitary mass lesion is rare and very difficult to be distinguished from a malignant tumor [43] .…”
Section: Disease Subtypes and Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple low-density lesions on enhanced CT are the most common radiologic finding in IgG4-related TIN, but diffuse bilateral renal swelling may be observed when severe renal failure is a contraindication for the administration of contrast medium. Kidney abnormalities on CT imaging have been observed in nearly 70 % of patients with IgG4-RD (13)(14)(15)(16).…”
Section: Statement Of Ethicsmentioning
confidence: 99%